A Prospective, Active‐Controlled Split‐Face Clinical Trial Evaluating the Incremental Aesthetic Benefits of a Glutathione‐Containing Booster in a GHK ‐Conjugated Spicule Regimen - Seongmin Noh; Wonkyu Hong; Hosung Choi; Youngjin Park; Do Young Rhee (Journal of Cosmetic Dermatology, 2026)
ABSTRACT Background Transdermal delivery of hydrophilic peptides such as GHK remains limited by the stratum corneum barrier and the classical 500 Da rule. Spicule‐based systems and redox‐responsive linkages have been investigated as strategies to enhance epidermal delivery, but in vivo glutathione‐triggered cleavage remains a proposed mechanism rather than a clinically proven process. Objectives This study aimed to evaluate the clinical efficacy and safety of a GHK‐conjugated spicule regimen and to determine whether adding a multi‐ingredient, glutathione‐containing booster provides incremental aesthetic benefit compared with the shared base regimen alone. Methods In this prospective, active‐controlled split‐face clinical trial, 20 healthy Asian women received five weekly facial treatments. One prespecified facial side received the base regimen consisting of a GHK‐conjugated spicule system and base concentrate, while the contralateral side received the same base regimen plus a separate multi‐ingredient booster containing 1% glutathione. Wrinkle depth, pore parameters, skin elasticity, dermal density, surface roughness, and pigmentation were evaluated at baseline, after one and three treatment sessions, and 4 weeks after the fifth session. Between‐side comparisons were performed using change‐from‐baseline values, with prespecified primary endpoints, multiplicity adjustment, and effect‐size reporting. Results Both sides showed improvements from baseline. At the final timepoint, the intensive regimen produced greater improvements than the base regimen in periorbital wrinkle depth (−0.0144 vs. −0.0084 mm), nasolabial wrinkle depth (−0.0227 vs. −0.0173 mm), dermal density (+7.27 vs. +4.49), roughness (−1.23 vs. −0.73 μm), and mean pore volume (−0.0007 vs. −0.0005 mm 3 ). Multiplicity‐adjusted between‐side differences remained significant for the prespecified primary endpoints and secondary endpoints. No adverse effects were reported. Conclusion The GHK‐conjugated spicule base regimen improved multiple facial aging indicators, and the booster‐inclusive intensive regimen produced statistically greater short‐term improvements in this small split‐face trial. Because the booster was multi‐ingredient and the release mechanism was not directly measured in vivo, these findings should be interpreted as regimen‐level clinical evidence rather than proof of glutathione‐specific redox cleavage. Trial Registration TRN Registration Number: PRE20250909‐005